18 TILRR Functional Mutants Selectively Inhibit Inflammatory and Anti-Apoptotic Responses. (20th November 2012) - Neilan, M; Zhang, X; Steiner, T; Boyle, J; Francis, S; Haskard, D; Qwarnstrom, E
Abstract : Toll-like and IL-1 receptors control inflammatory responses. TILRR (Toll-like IL-1 Receptor Regulator), is an IL-1 co-receptor which associates with the type I IL-1 receptor (IL-1RI) to amplify activation of NF-kappaB and inflammatory responses. Earlier studies have demonstrated increased levels of TILRR in the atherosclerotic plaque. Further, that injection of a polyclonal anti-TILRR antibody, which blocks TILRR/IL-1RI association and reduces inflammatory responses, causes a 25% decrease in plaque formation in ApoE-/- mice on a high fat diet. Alanine scanning mutagenesis identified two sites within the TILRR core protein, which allow distinct control of Il-1 activities. The R425A substitution blocks enhanced cell survival, but functions as wild-type in relation to inflammatory responses. In contrast, a D448A substitution reduces MyD88-dependent inflammatory responses, but has no impact on cell survival [1]. Current studies use peptides designed to block these distinct functional sites to further analyse consequences of selective inhibition on downstream events. Results show a successive reduction in inflammatory responses by the peptide designed to block D448 dependent interactions, with no effect of the peptide targeting anti-apoptotic signals or a non-specific control. Ongoing studies are testing the effect of the peptides on IL-1-induced cell survival. 1. Zhang, X., et al., JBC, 2012, doi:10.1074/jbc.C111.321711